2022
DOI: 10.1080/13880209.2021.2019283
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study on the relieving effect of Lilium brownii on the intestinal flora and metabolic disorder in p -chlorphenylalanine induced insomnia rats

Abstract: Context The bulb of Lilium brownii F. E. Brown (Liliaceae) (LB) is a common Chinese medicine to relieve insomnia. Objective To investigate the molecular mechanism of LB relieving insomnia. Materials and methods Insomnia model was induced by intraperitoneally injection p -chlorophenylalanine (PCPA) in Wistar rats. Rats were divided into three groups: Control, PCPA (400 mg/kg, i.p. 2 days), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…The alteration of the gut microbiota in insomnia rats was accompanied by the disorders of serum metabolome, as described in other studies [ 38 40 ]. Correlation analysis demonstrated that the metabolites elevating in insomnia rats, such as Amide c18, Benzoyl chloride, Cytosine, and N, n-dimethylarginine were positively associated with the abundance of Clostridium XlVa and Blautia , which characterized the insomnia rats.…”
Section: Discussionsupporting
confidence: 69%
“…The alteration of the gut microbiota in insomnia rats was accompanied by the disorders of serum metabolome, as described in other studies [ 38 40 ]. Correlation analysis demonstrated that the metabolites elevating in insomnia rats, such as Amide c18, Benzoyl chloride, Cytosine, and N, n-dimethylarginine were positively associated with the abundance of Clostridium XlVa and Blautia , which characterized the insomnia rats.…”
Section: Discussionsupporting
confidence: 69%
“…The gut microbiota plays a crucial role in numerous host physiological processes and the development of various diseases ( Li et al, 2020 ; Si et al, 2022b ; Zhou et al, 2022a ). Many studies have identified the relationship between gut microbiota and NCDs ( Arnoriaga-Rodríguez and Fernández-Real, 2019 ; Liu et al, 2020 ; Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…L. brownii is used directly by herbalists as a treatment for symptoms such as coughing and insomnia. [23] In a previous study conducted by our team, it was discovered that L. brownii extract had a significant ameliorative effect on PCPA-induced insomnia in rats by modulating a variety of intestinal flora in rats, including Porphyromonadaceae, Lactobacillus and Escherichia, as well as modulating multiple metabolic pathways in the hypothalamus, serum and hippocampus, such as tryptophan metabolism, arachidonic acid metabolism, and serotonergic synapse, etc.. [1,2] Additionally, our subsequent characterization of the chemical composition of L. brownii led to the identification of several new phenolic acid glycerides and steroidal saponins. The wide range of anticancer activities of steroidal saponins from genus Lilium [24,25] prompted us to screen two new steroidal saponins for anticancer activities.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Baihe Dihuang decoction, a classical Chinese prescription which is composed of LILII BULBUS and REHMANNIAE RADIX, has been used for thousands of years to treat emotional diseases, and the medicinal diet of Baihe Lianzi porridge was used in Chinese folk for regimen and health care. [2] L. brownii has been extensively studied for its chemical composition and pharmacological activity because of its broad development prospects in edible and medicinal areas. Phytochemical studies have shown that L. brownii contain steroidal saponins, [3,4] sterol, [5] phenolic glyceride, [6] flavonoids, [7] phenylpropanoid, [8] alkaloids [9] and polysaccharides.…”
Section: Introductionmentioning
confidence: 99%